2012
DOI: 10.1088/0957-4484/23/38/385703
|View full text |Cite
|
Sign up to set email alerts
|

Comparative structural and electronic studies of hydrogen interaction with isolated versus ordered silicon nanoribbons grown on Ag(110)

Abstract: We have investigated the geometry and electronic structure of two different types of self-aligned silicon nanoribbons (SiNRs), forming either isolated SiNRs or a self-assembled 5 × 2/5 × 4 grating on an Ag(110) substrate, by scanning tunnelling microscopy and high resolution x-ray photoelectron spectroscopy. At room temperature we further adsorb on these SiNRs either atomic or molecular hydrogen. The hydrogen absorption process and hydrogenation mechanism are similar for isolated or 5 × 2/5 × 4 ordered SiNRs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 34 publications
6
31
0
Order By: Relevance
“…Their edges are passivated by H while their surfaces are kept pristine because the surfaces are less reactive than the edges. 76 It has been reported that 7-ASiNR is a paramagnetic semiconductor with a band gap of ~0.56 eV. 56,58 The semiconducting ASiNR is chosen because it is expected that the adsorption of gas molecules has a much smaller effect on the electronic properties of zigzag SiNRs (ZSiNRs) which are metallic.…”
Section: Resultsmentioning
confidence: 99%
“…Their edges are passivated by H while their surfaces are kept pristine because the surfaces are less reactive than the edges. 76 It has been reported that 7-ASiNR is a paramagnetic semiconductor with a band gap of ~0.56 eV. 56,58 The semiconducting ASiNR is chosen because it is expected that the adsorption of gas molecules has a much smaller effect on the electronic properties of zigzag SiNRs (ZSiNRs) which are metallic.…”
Section: Resultsmentioning
confidence: 99%
“…The calculations show that at adequate levels of H insertion, it forms a freestanding decorated silicane structure in separating the silicene sheet from its growth substrate. This process has been experimentally demonstrated in the case of extracting silicene nano ribbons from Ag substrates and is yet to be extended to sheets . Li was observed to have a preferential state of bonding on top of silicene proving inadequate for exfoliation purposes .…”
Section: Realizing 2d Elemental Sheetsmentioning
confidence: 99%
“…Thus far, freestanding silicene has not been synthesized. Most of the silicene structures were grown on Ag surfaces89101112131415161718, with a few successes on ZrB 2 19 and Ir20. Yet, interaction with the substrate may render it rather difficult to probe the intrinsic properties of silicene21222324.…”
mentioning
confidence: 99%